Diagnostic criteria for Susac syndrome - Kleffner, Ilka Anna Elisabeth; Dörr, Jan; Ringelstein, Marius; Gross, Catharina C.; Böckenfeld, Yvonne; Schwindt, Wolfram; Sundermann, Benedikt; Lohmann, Hubertus; Wersching, Heike; Promesberger, Julia; Königsmarck, Natascha von; Alex, Anne; et al. (Journal of neurology, neurosurgery, and psychiatry, 2016)
Background Susac syndrome is characterised by the triad of encephalopathy with or without focal neurological signs, branch retinal artery occlusions and hearing loss. Establishment of the diagnosis is often delayed because the triad is complete only in a minority of patients at disease onset. This leads to a critical delay in the initiation of appropriate treatment. Our objective was to establish criteria for diagnosis of either definite or probable Susac syndrome. - Method The establishment of diagnostic criteria was based on the following three steps: (1) Definition of a reference group of 32 patients with an unambiguous diagnosis of Susac syndrome as assessed by all interdisciplinary experts of the European Susac Consortium (EuSaC) team (EuSaC cohort); (2) selection of diagnostic criteria, based on common clinical and paraclinical findings in the EuSaC cohort and on a review of the literature; and (3) validation of the proposed criteria in the previously published cohort of all Susac cases reported until 2012. - Results Integrating the clinical presentation and paraclinical findings, we propose formal criteria and recommend a diagnostic workup to facilitate the diagnosis of Susac syndrome. More than 90% of the cases in the literature fulfilled the proposed criteria for probable or definite Susac syndrome. We surmise that more patients could have been diagnosed with the recommended diagnostic workup. - Conclusions We propose diagnostic criteria for Susac syndrome that may help both experts and physicians not familiar with Susac syndrome to make a correct diagnosis and to prevent delayed treatment initiation.
Gesehen am 13.05.2020